Implementation of the Community Education Quality Assurance System Based on the 8 National Education Standards at PKBM Hang Tuah, Pekanbaru City - Zahra Nur Adilla; Rahmat Fahmi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the implementation of quality assurance systems in community education based on National Education Standards at PKBM Hang Tuah in Pekanbaru City. Nonformal education plays an important role in expanding access to education for communities excluded from formal schooling. The literature review highlights the importance of quality assurance, the application of eight national education standards, and the role of community learning centers in equivalency education. The research method applies a literature review supported by field data including tutor interviews, learner interviews, classroom observations, and curriculum document analysis. The findings show structured institutional management, adequate education financing, participatory learning processes, and improved learner competencies. The conclusion indicates that quality assurance implementation contributes to improving the quality of equivalency education programs.